Distributed vibration isolation and manual dexterity of anti-vibration gloves: is there a correlation?. Issue 6 (2nd June 2020) - Yao, Yumeng; Rakheja, Subhash; Marcotte, Pierre
Abstract: This study focuses on the integrated performance of anti-vibration (AV) gloves in terms of manual dexterity and distributed palm and fingers' vibration transmissibility. Experiments were designed to measure vibration transmission and manual dexterity performance of 10 different gloves using 15 subjects. The results showed all gloves impeded manual dexterity, while five gloves satisfied the AV glove screening criteria. Glove type yielded a significant effect on manual dexterity ( p < 0.001) and vibration transmissibility ( p ≤ 0.001). Manual dexterity decreased nearly linearly with an increase in glove thickness ( p < 0.05), while palm and fingers' vibration transmissibility in high-frequency range was negatively correlated with glove thickness ( R 2 > 0.70). A strong correlation was evident between glove material stiffness and the H-frequency range palm vibration transmissibility ( R 2 ≥ 0.8). While the vibration isolation of a glove is strongly related to material properties at the palm, the dexterity performance is dependent on design factors such as thickness and bulkiness. Practitioner summary Anti-vibration gloves are used to isolate hand from power tools vibration, while these may adversely affect manual dexterity. Vibration isolation was correlated with material properties and thickness, while dexterity was correlated with thickness alone. Glove thickness is a vital parameter for realising a compromise between vibration isolation and manual dexterity. Abbreviations: HTV: hand-transmitted vibration; AV: anti-vibration; MANOVA: multivariate analysis of variance; TR: vibration transmissibility; ASTM: ASTM F2010 standard test; Minnesota: Two-Hand Turning and Placing Minnesota test; rANOVA: repeated-measures analysis of variance; rms: root mean square; CoV: coefficient of variations; S: score